Constraining SN Ia Progenitors from the Observed Fe-peak Elemental Abundances in the Milky Way Dwarf Galaxy Satellites - Alexander, Ryan; Vincenzo, Fiorenzo
Chemical abundances of iron-peak elements in the red giants of ultra-faint dwarf galaxies (UFD) and dwarf spheroidal galaxies (dSph) are among the best diagnostics in the cosmos to probe the origin of Type Ia Supernovae (SNe Ia). We incorporate metallicity-dependent SN Ia nucleosynthesis models for different progenitor masses in our inhomogeneous galactic chemical evolution model, i-GEtool, to recreate the observed elemental abundance patterns and their spread in a sample of UFD and dSph galaxies with different average metallicities and star formation histories. Observations across different environments indicate that [Mn/Mg] increases on average with metallicity while [Ni/Mg] remains nearly constant. Chemical evolution models assuming SN Ia progenitors with Chandrasekhar mass (MCh) produce similar to identical [Mn/Mg]-[Fe/H] and [Ni/Mg]-[Fe/H] patterns to those observed in the examined UFD and dSph galaxies, without needing to invoke a substantial fraction of sub-MCh progenitors that changes across the different environments, as claimed by some previous chemical evolution studies. We note though that the observed UFD sample is still statistically poor to draw firm conclusions. Sub-MCh progenitors in our dSph models systematically under produce both [Mn/Mg] and [Ni/Mg], with the 1M⊙ model explaining a number of outliers in [Ni/Fe], while the outliers in [Mn/Mg] require higher sub-MCh progenitor masses. The average dispersion of [X/Mg] from our UFD model ranges between 0.20 and 0.25 for iron-peak elements, with the exception of [Sc/Mg] that has σ≈0.39.